1999
DOI: 10.1242/jcs.112.6.887
|View full text |Cite
|
Sign up to set email alerts
|

CFTR channel insertion to the apical surface in rat duodenal villus epithelial cells is upregulated by VIP in vivo

Abstract: cAMP activated insertion of the cystic fibrosis transmembrane conductance regulator (CFTR) channels from endosomes to the apical plasma membrane has been hypothesized to regulate surface expression and CFTR function although the physiologic relevance of this remains unclear. We previously identified a subpopulation of small intestinal villus epithelial cells or CFTR high expressor (CHE) cells possessing very high levels of apical membrane CFTR in association with a prominent subapical vesicular pool of CFTR. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Unlike villus enterocytes of the small intestine, CHEs lack the typical absorptive markers that are present on the brush border, including sucrase isomaltase, lactase, alkaline phosphatase, but they express high levels of the vATPase (vacuolar H + -ATPase proton pump) and CFTR. Interestingly, villus CHEs display robust trafficking of endosomal associated CFTR into the brush border upon cAMP, cGMP, Ca 2+ stimulation, and low pH consistent with a secretory profile [ 41 , 42 , 43 , 44 ]. We observed high levels of CFTR on the brush border of villus CHE cells in human MVID duodenal tissues resulting from loss of MYO5B mutations [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike villus enterocytes of the small intestine, CHEs lack the typical absorptive markers that are present on the brush border, including sucrase isomaltase, lactase, alkaline phosphatase, but they express high levels of the vATPase (vacuolar H + -ATPase proton pump) and CFTR. Interestingly, villus CHEs display robust trafficking of endosomal associated CFTR into the brush border upon cAMP, cGMP, Ca 2+ stimulation, and low pH consistent with a secretory profile [ 41 , 42 , 43 , 44 ]. We observed high levels of CFTR on the brush border of villus CHE cells in human MVID duodenal tissues resulting from loss of MYO5B mutations [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…CFTR High Expresser (CHE) Cells Are Present in cMYO5BKO and cMYO5B-SGK1-DKO Mice CHE cells were first reported in localization studies of CFTR in the human and rat intestine in 1995 [39] but were not found in mice under homeostatic conditions [40]. CHEs are unique rare enterocytes (~1-2% total epithelial cells) found both in crypts and villi but more predominantly found scattered along the villi of duodenum and jejunum where they express unusually high levels of CFTR both in subapical endosomes and on the brush border [39,[41][42][43][44]. Unlike villus enterocytes of the small intestine, CHEs lack the typical absorptive markers that are present on the brush border, including sucrase isomaltase, lactase, alkaline phosphatase, but they express high levels of the vATPase (vacuolar H + -ATPase proton pump) and CFTR.…”
Section: Cftr High Expresser (Che) Cells Are Present In Cmyo5bko and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is also known that the G‐protein‐cAMP‐PKA signalling, as downstream factors of adrenergic and muscarinic receptors, mediate sympathetic and parasympathetic effects on cardiomyocytes. The activation of PKA via neurohumoral stimulation of β‐adrenergic receptors could increase the conduction in normal ventricular myocardium and modulate cardiac electrophysiology, 33 indicating the possible roles of alterations of PKA and adrenergic stimulation in arrhythmic events. 34 , 35 Moreover, catecholamine level in blood can be increased by fever, 36 suggesting an involvement of activation of adrenoceptor/cAMP/PKA signalling at febrile state.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of intracellular cAMP results in the activation of downstream targets that leads to CFTR activation and secretory diarrhea. [ 77 , 102 ] Traveler's diarrhea Escherichia coli heat-stable enterotoxins (STa) binds to GC-C receptor in the membrane of enterocytes resulting in cGMP increase and consequent activation of downstream targets, including PKGII, that promotes CFTR activation and secretory diarrhea. [ 91 ] 2.…”
Section: Mitochondria Rich (Mr) Cells/ionocytesmentioning
confidence: 99%